Rajasthan Approach to the Fifth Five Year Plan - Planning Commission (Planning Commission, 1972)
Rajasthan's approach to the Fifth Five Year Plan has necessarily to be bold and pragmatic. the constraints imposed by years of backwardness and geographical disadvantages have left the State far behind in the race of economic development. While the achievements of the twenty-two years of planning could not be said to be inconsiderable, the fact remains that Rajasthan continues to be one of the poorest States in the country and a long hard road still lies ahead for it. The Approach Paper of the State Government seeks to highlight the achievements made by the State in the face of natural handicaps like the existence of huge areas of desert and recurrent famines, and to indicate spheres where significant growth and economic development can be achieved. In order to bring the State's economy to the level of the national average, strenuous efforts will be needed, and even then, it is anticipated that only the position of the national average at the end of the Fourth Five Year Plan would be achieved in Rajasthan with a rate of growth of 7% during the Fifth Five Year Plan.
Planning Department Government of Rajasthan